JENIS VEGETASI DAN KARAKTERISTIK LAHAN DI KAWASAN HUTAN LINDUNG PULAU TARAKAN - Sutrisno, Adi; Kartodihardjo, Hariadi; Darusman, Dudung; Nugroho, Bramasto (Jurnal Hidrolitan, 2011)
ABSTRACTThis study aimed to describe the type of vegetation and soil fertility status in the protected forest areas of Tarakan Island (HLPT). The results showed that: (1) the dominant vegetation types in HLPT belong to a group of Dipterocarpaceae, such as meranti (Shorea sp), keruing (Dipterocarpus), Resak (Vatica sp), Merawan (Hopea sangal) and Tengkawang (Shorea pinanga); (2) The soil types in the HLPT area are dominated by Podsolic, with a very acid soil category to sour, having a low ability in holding and exchanging kation, total nitrogen levels from very low to low, levels of C-Organic from very low to high, the phosphorus (P) content available classified as very low to very high and the potassium (K) content available relatively moderate to very high, and (3) the soil fertility status of HLPT is very low to low with HLPT soil texture in form of clay, sandy loam and loamy sand.